2017
DOI: 10.1177/2396987317721865
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of mechanical thrombectomy using stent retriever after intravenous tissue plasminogen activator compared with intravenous tissue plasminogen activator alone in the treatment of acute ischaemic stroke due to large vessel occlusion in Spain

Abstract: Introduction: To assess the cost-effectiveness of stent-retriever mechanical thrombectomy and intravenous tissue plasminogen activator compared with intravenous tissue plasminogen activator alone in patients with acute ischaemic stroke due to large vessel occlusions in Spain. Materials and methods: Clinical data were taken from the SWIFT PRIME clinical trial. A lifetime Markov state transition model defined by the modified Rankin Scale score was developed to estimate costs and health outcomes (life years gaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
0
17
1
3
Order By: Relevance
“…In a Spanish cost analysis study, also using real-life resources, the cost of MT including predominantly SR devices with consumables and staffing was equivalent to £5,980. 23 In a Norwegian health technology assessment, the estimated costs of MT including the procedure, diagnostical imaging and transport were estimated to be £5,919, substantially lower that the estimate in our study of these same components of £8,750. 24 The higher MT costs in some of the economic analyses above compared with this current study, where a mixture of devices were used, could be related to the predominant use of SR devices for MT.…”
Section: Discussioncontrasting
confidence: 63%
“…In a Spanish cost analysis study, also using real-life resources, the cost of MT including predominantly SR devices with consumables and staffing was equivalent to £5,980. 23 In a Norwegian health technology assessment, the estimated costs of MT including the procedure, diagnostical imaging and transport were estimated to be £5,919, substantially lower that the estimate in our study of these same components of £8,750. 24 The higher MT costs in some of the economic analyses above compared with this current study, where a mixture of devices were used, could be related to the predominant use of SR devices for MT.…”
Section: Discussioncontrasting
confidence: 63%
“…According to WFR, on the first day after treatment, patients showed the greatest difficulties with mobility and locomotion, namely with sitting on a toilet and going up the stairs. The smallest problem was communication, which is associated with the emerging aphasia, which is the second most frequent symptom of focal brain damage according to the authors [33]. The distribution of results on this scale was very similar on the 1 st and 9 th day of treatment.…”
Section: Discussionmentioning
confidence: 75%
“…Most of the economic evaluations concluded that EVT was a dominant treatment option (i.e., higher QALYs and lower costs) for patients with ischemic stroke, while the rest reported its positive cost-effectiveness (i.e., ICER falls below the WTP/QALY threshold for various jurisdictions), including late window EVT (studies listed in Supplementary Table X ). The gains in QALYs from these studies ranged from 0.54 ( 43 ) to 2.51 ( 46 ) over the lifetime horizon. However, positive cost-effectiveness outcomes that are built upon efficacy outcomes from clinical trials may misinform clinical and policy decision-making, thereby leading to inappropriate management of patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 95%